2003
DOI: 10.1111/1539-6924.00358
|View full text |Cite
|
Sign up to set email alerts
|

The Speeding Attitude Scale and the Role of Sensation Seeking in Profiling Young Drivers at Risk

Abstract: Seven driving attitude scales representing driving behaviors and beliefs about driving were created and initially validated using 257 undergraduate students (168 females, 89 males) in Study 1. However, the Speeding Attitude Scale (SAS) accounted for most of the strength of the intercorrelations among these scales and discriminant classification analyses showed that SAS dominated the other scales as a sufficient explanation for having speeding tickets. Study 2, using 180 students (75 males, 105 females), replic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
28
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(31 citation statements)
references
References 17 publications
3
28
0
Order By: Relevance
“…Like other studies, a significant relationship was noticed between two variables of risk taking attitude and risky driving behaviors,[3134] It is unlike other studies carried out upon this respect which showed that attitude is predictive of risk taking,[2125] in the present study, risky driving behaviors are a stronger predictors of risk taking in Iranian drivers. However, in these studies it has been mentioned because attitude and behavior are measured simultaneously, it is difficult to claim that attitude is predictive of risk taking.…”
Section: Discussionsupporting
confidence: 56%
“…Like other studies, a significant relationship was noticed between two variables of risk taking attitude and risky driving behaviors,[3134] It is unlike other studies carried out upon this respect which showed that attitude is predictive of risk taking,[2125] in the present study, risky driving behaviors are a stronger predictors of risk taking in Iranian drivers. However, in these studies it has been mentioned because attitude and behavior are measured simultaneously, it is difficult to claim that attitude is predictive of risk taking.…”
Section: Discussionsupporting
confidence: 56%
“…Also, males consider traffic violations less dangerous than females. Whissell and Bigelow (2003), evinced that accidents could be explained as function of gender, also risky driving bears a more influential factor in male adolescents' injuries and deaths.…”
Section: Gendermentioning
confidence: 99%
“…However, in some of the empirical studies that tested the hypothesis about attitudes as a main determinant of behaviour, it was found that attitudes provide only a partial and limited explanation of intentions or behaviour. For example, Whissell and Bigelow (2003) found no link between attitudes towards speeding and actual reported collisions. By studying drivers' compliance with speed limits, Elliott, Armitage, and Baughan (2003) found very little relationship between attitude and intention.…”
Section: Introductionmentioning
confidence: 95%
“…The Theory of Planned Behaviour (TPB) has a long tradition of being used in explaining individual factors that influence road user safety behaviour (e.g. Armitage and Conner 2001;Conner et al 2007;Elliott, Armitage, and Baughan 2003;Parker et al 1992;Whissell and Bigelow 2003). The model, by definition, only deals with planned behaviour and does not examine wider contextual influences (Avineri 2012).…”
Section: Introductionmentioning
confidence: 99%